2009
DOI: 10.1007/s10461-009-9632-0
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Infant Male Circumcision as Part of HIV Prevention and Male Reproductive Health Efforts in Gaborone, Botswana, and Surrounding Areas

Abstract: Correspondence to: Rebeca M. Plank, rplank@partners.org. Disclaimer: The findings and conclusions in this article are those of the authors and do not necessarily represent the views of the US Centers for Disease Control and Prevention. Adult male circumcision reduces a man's risk for heterosexual HIV acquisition. Infant circumcision is safer, easier and less costly but not widespread in southern Africa. Questionnaires were administered to sixty mothers of newborn boys in Botswana: 92% responded they would circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 10 publications
6
39
0
Order By: Relevance
“…Previous acceptability studies have indicated several common barriers to EIMC services in east and Southern Africa including: fear of pain, bleeding, death and other adverse events associated with the procedure, and cultural opposition to EIMC ( Ref 17]. The most frequent facilitators reported are parental belief in protection from HIV and STI acquisition and improved hygiene ( Ref 15,18,19]. Limitations of acceptability studies published to date include: small sample size, data collection when adult MMC programs were nascent, only mothers included, and convenience sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Previous acceptability studies have indicated several common barriers to EIMC services in east and Southern Africa including: fear of pain, bleeding, death and other adverse events associated with the procedure, and cultural opposition to EIMC ( Ref 17]. The most frequent facilitators reported are parental belief in protection from HIV and STI acquisition and improved hygiene ( Ref 15,18,19]. Limitations of acceptability studies published to date include: small sample size, data collection when adult MMC programs were nascent, only mothers included, and convenience sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 showed that the highest percentage of HIV infection was found in 31-40 years old group (43.5%), in which this age group is in their productive age, while the lowest percentage was found in 51-60 years old group (3.5%). Plank et al, (2010) indicated that the highest HIV infection was in the 15-49 years old group and they were heterosexuals ranged from 50% to 75%. Study conducted in Botswana, Africa showed that only 15% men had neonatal circumcision.…”
Section: Resultsmentioning
confidence: 99%
“…World Health Organization (WHO) estimates that in 1999, there will be 340 million new cases of sexual transmitted infections every year (Katz and Wright, 2008;Plank, 2010). HIV is transmitted by several ways, such as horizontally by sexual practice and infected blood or vertically, which is from infected mothers to their babies (Plank, 2010;Roloff et al, 2011).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
See 2 more Smart Citations